2020
DOI: 10.1002/adbi.202000008
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthetic, Xeno‐Free Biomimetic Surface for Serum‐Free Expansion of Human Mesenchymal Stromal Cells

Abstract: diseases for which no therapies currently exist including graft-versus-host disease, [1,2] autoimmune diseases, [3] liver diseases, [4] orthopedic injuries, [5] cardiovascular diseases, [6] and cancer. [7] But despite high interest and a large number of clinical trials, only three hMSC-based therapies have been clinically approved yet. This might be largely due to the fact that their medical application still faces many challenges including heterogeneity in therapeutic targets, routes of delivery, range of dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…We and others have previously reported that BM-MSCs expanded in serum-free medium show a smaller cell size than MSCs expanded in serum-containing medium 20,21 . Similarly, cells isolated using the isoMATRIX in combination with xeno-/serum-free medium were significantly smaller (16 ± 0.8 µm) compared to those isolated under serum-containing conditions (20 ± 0.8 µm; Fig.…”
Section: Xeno-/serum-free Isolation Of Bm-mscs With Isomatrix Results In a 4-fold Increase In Isolated Cell Number And Significant Decreamentioning
confidence: 62%
See 2 more Smart Citations
“…We and others have previously reported that BM-MSCs expanded in serum-free medium show a smaller cell size than MSCs expanded in serum-containing medium 20,21 . Similarly, cells isolated using the isoMATRIX in combination with xeno-/serum-free medium were significantly smaller (16 ± 0.8 µm) compared to those isolated under serum-containing conditions (20 ± 0.8 µm; Fig.…”
Section: Xeno-/serum-free Isolation Of Bm-mscs With Isomatrix Results In a 4-fold Increase In Isolated Cell Number And Significant Decreamentioning
confidence: 62%
“…We previously developed myMATRIX MSC, a surface coating optimized for MSC expansion, which showed suboptimal support during MSC isolation from bone marrow aspirates (data not shown). To identify a new biomatrix that can aid MSC isolation, we selected 12 candidates, previously identified from our in-house screening tool (screenMATRIX), that supported efficient MSC expansion 20 . In preliminary isolation tests, the use of a biomatrix composed of dextran sulfate and a fibronectin-derived peptide-conjugate resulted in the best cell morphology and highest isolated cell number (data not shown).…”
Section: Xeno-/serum-free Isolation Of Bm-mscs With Isomatrix Results In a 4-fold Increase In Isolated Cell Number And Significant Decreamentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5,6 ] Alternatively, synthetic materials can also be employed. [ 7–12 ] While proteins or ECM extracts can enable effective cell adhesion and most faithfully mimic the cellular microenvironments, synthetic materials offer more defined substrates with low batch‐to‐batch variation facilitating their applications especially for clinical purposes. [ 13,14 ]…”
Section: Figurementioning
confidence: 99%
“…Many primary and stem cells are anchorage‐dependent cell types and require a certain degree of adhesion to a solid culture support to ensure cell survival, growth, and development in vitro. [ 10,15–17 ] To enable cell adhesion, synthetic materials can be modified with peptides ligands, which are specific adhesion sequences derived from ECM proteins. The first reported and most frequently used sequence Arg‐Gly‐Asp (RGD) has been identified by Ruoslahti and colleagues in 1984.…”
Section: Figurementioning
confidence: 99%